PELATIHANBUSINESS PLANPENGEMBANGAN TOMAT DI DUSUNPULUHAN,BANYUSIDI, PAKIS, MAGELANG,JAWA TENGAH - Muhammad Hasyim (UII, 2014)
Entrepreneurshas a place in society as a professionthatcan not simply be able tomake improvements and changes in the quality of life for themselves and society, butalso entrepreneurs also been shown to play a significant role indelivering the quality ofpeople's self and nation. Business / entrepreneurshipwould require planning for growthoptimism and developments with priorities. The increase in the number ofentrepreneurs is also beingconducted, one that can be use is to provide training relatedto the design of a business plan that is given to housewife in Puluhan village. Theprogram is done in order to motivate the mother/housewifes in Puluhan village tobecome entrepreneurs and maximize the value of which is selling tomatoes Villagecommodity that can be processed into more valuable products such as preserves andketchup.